Systems pharmacology-based optimization of Ma Xing Shi Gan components for the enhanced treatment of chick health issues caused by infectious bronchitis virus - Liu, Huixin; He, Yang; Wang, Chenchen; Wei, Xiaofang; Chen, Jiayi; Wang, Kaijun (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionInfectious bronchitis virus (IBV) imposes severe economic burdens on the poultry industry, and current treatments face challenges in efficacy and sustainability, necessitating the development of novel therapeutic strategies. To address this, this study employed the Traditional Chinese Medicine Inheritance Computing Platform (TCMICS) to collect clinical prescriptions for IBV treatment, based on which two optimized versions of the traditional Chinese medicine Maxing Shigan Decoction (MXSG), namely MXSG-mix1 and MXSG-mix2, were designed. In vitro cell culture and in vivo chicken model experiments were then carried out, including egg testing, clinical symptom observation, immune function analysis, and viral load quantification, to assess the antiviral activity of the optimized formulations.MethodsTo explore the underlying mechanisms, liquid chromatography-mass spectrometry (LC-MS) was combined with network pharmacology to identify 28 active compounds in MXSG-mix and 47 key genes involved in viral replication, inflammation, and apoptosis pathways. Furthermore, molecular docking and RT-qPCR were performed, which confirmed that MXSG-mix downregulated BCL2 expression and interacted with AKT1 and CASP3, thus inhibiting IBV-induced cell apoptosis.Results and discussionThe results showed that both MXSG-mix1 and MXSG-mix2 exhibited superior anti-IBV activity compared to traditional MXSG, effectively reducing viral load and improving immune responses in vivo. In conclusion, integrating TCMICS, LC-MS, and network pharmacology offers a novel paradigm for developing veterinary TCM formulations. The optimized MXSG-mix shows potential as an effective, multi-target therapeutic against IBV, providing valuable insights for future anti-viral drug development in poultry medicine.